Effect of Ayurveda Interventions in The Management of Chronic Plaque Psoriasis: A Case Report. - Sharma, Diksha; Garg, Ish; Yadav, Sujata (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Psoriasis is one of many prevalent skin conditions. According to Ayurveda, Kushtha Roga encompasses a wide range of skin conditions. All kushtha are Tridoshaj in nature, involving the four Dushyas (body tissues) i.e., Tvak (skin), Rakta (blood), Mansa (muscle), and Lasika (lymph). Psoriasis can be correlated with Ekkushtha in Ayurveda due to resemblance of its clinical features. In modern medicine, corticosteroids, PUVA Therapy, and topical therapies are all employed. Each has its own negative effects. Methodology: In the current case study, patients were having complaints of reddish white scaly patches covering her entire body with itching. She received a multimodal treatment regimen that included Shaman Chikitsa (internal medication) with various Ayurvedic formulations as internal medications, medicated oil for external application, along with Virechan karma (purgation therapy) as Shodhana Chikitsa (purification treatment). Result: The regimen showed promising results in treating the case of psoriasis. After following the prescribed Ayurvedic diet and treatment plan, the patient saw a 90% reduction in symptoms and related concerns. Discussion: The present study emphasizes the role of Ayurveda in bringing a positive result in the management of chronic plaque psoriasis.